Differential effects of mesalazine formulations on thiopurine metabolism through thiopurine S‐methyltransferase inhibition. Issue 8 (29th January 2021) - Morikubo, Hiromu; Kobayashi, Taku; Ozaki, Ryo; Okabayashi, Shinji; Kuronuma, Satoshi; Takeuchi, Osamu; Shiba, Tenyo; Kiyohara, Hiroki; Matsubayashi, Mao; Sagami, Shintaro; Nakano, Masaru; Ikezaki, Osamu; et al.
Abstract: Background and Aim: Thiopurines are often used in combination with mesalazine for the treatment of ulcerative colitis (UC). Mesalazine formulations are delivered to the digestive tract by various delivery systems and absorbed as 5‐aminosalicylic acid (5‐ASA). 5‐ASA is known to inhibit thiopurine S ‐methyltransferase (TPMT) activity and to affect thiopurine metabolism. There have been no studies comparing TPMT inhibition by multimatrix mesalazine (MMX) with other formulations. We investigated the difference in TPMT inhibition by different mesalazine formulations and prospectively confirmed the clinical relevance. Methods: Plasma concentrations of 5‐ASA, N ‐acetyl‐5‐aminosalicylic acid ( N ‐Ac‐5‐ASA), and TPMT activities were measured in UC patients receiving various mesalazine formulations (time‐dependent or pH‐dependent mesalazine or MMX) as monotherapy. Patients already on both time‐dependent or pH‐dependent mesalazine and thiopurines switched their mesalazine to MMX, examining 6‐thioguanine nucleotide (6‐TGN) and 6‐methylmercaptopurine (6‐MMP) 0 and 8 weeks after switching. Clinical relapse after switching was also monitored for 24 weeks. Results: Plasma 5‐ASA and N ‐Ac‐5‐ASA levels were significantly higher in patients receiving time‐dependent mesalazine ( n  = 12) compared with pH‐dependent mesalazine ( n  = 12) and MMX ( n  = 15), accompanied by greater TPMT inhibition. Prospective switching from time‐dependent mesalazine to MMX decreased 6‐TGN levels, increased those of 6‐MMP, and increased 6‐MMP/6‐TGN ratios. Furthermore, this resulted in significantly more relapses than switching from pH‐dependent mesalazine to MMX. Conclusions: Time‐dependent mesalazine has higher plasma 5‐ASA and N ‐Ac‐5‐ASA levels and greater TPMT inhibition than MMX. Therefore, switching from time‐dependent mesalazine to MMX may lead to an increase of 6‐MMP/6‐TGN, which may reduce the clinical effectiveness of thiopurines, warranting close monitoring after switch.